The Sexual Objectification of National Team Athletes in Generative AI Photos Created by Fans: A Semiotic Analysis - Amadia Candra Arumdafta; Lintang Ratri Rahmiaji (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2026)
The advancement of artificial intelligence (AI) technology has facilitated the emergence of AI-generated photo content, giving rise to a social media trend in which users create images depicting themselves alongside their idols. This trend is originated within the fan community of the Indonesian National Football Team athletes in various intimate scenarios. This study aims to examine the forms of sexual objectification directed at these athletes. Employing a qualitative approach, this research utilizes Roland Barthes’ semiotic analysis alongside Objectification Theory. The data consist of AI-generated photo content circulating on social media, representing the male bodies of Indonesian National Football Team athletes as constructed by fans. The findings reveal that such content frames athletes’ bodies as sexual objects, detached from their achievements and professional identities. These representations contribute to the normalization of an ideology in which athletes, as public figures, are rendered consumable within private and sexualized contexts. Furthermore, this form of objectification has evolved into a recurring pattern within digital fan culture, continuously reproduced and normalized through AI technologies on social media.